The role of share repurchases for firms' social and environmental sustainability - Vaupel, Mario (Journal of business ethics, 2023)
This article embarks on ethical trade-offs at the sustainability/finance interface by contrasting shareholders' interest in short-term financial returns with society's interest in counteracting ecological and social grievances. Scrutinizing share repurchases, we investigate a firm's communicated sustainability orientation (i.e., its environmental and social value orientation) as well as its environmental and social sustainability performance. Our results are based on a large-scale panel dataset of 491 U.S. firms observed from 2004 to 2016. The dataset combines share buyback data with sustainability orientation scores from shareholder letters and sustainability performance ratings. The econometric models suggest no association between social value orientation and repurchase volumes, but a significantly negative relationship between environmental value orientation and buybacks in a cubic form. Executive stock options partially attenuate this relationship. Share repurchases in turn negatively affect future environmental and social performance. This study grasps the consequences of firms' short-term shareholder satisfaction and discusses its ethical implications in the context of firms' contribution to sustainable development, thereby providing important insights to the business ethics discourse.